Changes in Land Use/Land Cover Patterns in Indonesia’s Border and their Relation to Population and Poverty - Fransiscus Xaferius Herwirawan; Cecep Kusmana; Endang Suhendang; Widiatmaka Widiatmaka (Jurnal Manajemen Hutan Tropika, 2017)
This study analyzes the pattern and change of land use and land cover (LULC) during 2000−2015 and its relation to population and poverty in the semi-arid region of Indonesia in Timor Island, on the country border to Republic Dominica Timor Leste (RDTL). The analyzes employ visual interpretation using GIS to aid classification of Landsat imagery and find 14 classes of LULC.  The matrix of LULC change for the 15 years period indicates a substantial deforestation in which 1,309 ha or 13% of the forest in year 2000 has disappeared. In detail, 2 ha (7%) of primary mangrove forest has became mixed farming and 1,307 ha (19%) of secondary forest has become shrub. Within the nonforest classification, 1,288 ha (17%) of shrub in 2000 has turned into savannah, and 15 ha (10%) of shrub swamp has turned into bare land, while at the same time human settlement has expanded by 118% from the settlement area in year 2000. Spatial pattern of LULC changes in the study area for 15 years are dispersed, and tend to remained in the middle area that dominated by mix agriculture. The forest cover is weakly associated with level of poverty and rural population in the study area. However, the two latter variables were not significantly associated with deforestation.